(untitled) (Journal of Medical & Health Sciences Review, 2025)
Herbal soap is often created by hand using only organic ingredients that are suitable for the environment and the skin. In this study S. fruticosa, a fleshy eternal halophytic shrub of Amaranthaceae family were used the objectives of the study is To investigate phytochemical, physiochemical, antimicrobial and antioxidant activities of the herbal formulations methanolic extract of Suaeda fruticosa was used with other ingredients. The current study suggested that formulated herbal soap has good texture, has organic odour, pleasant scent, pH of 7.92, good thumb impression effect for bacterial growth, and it have good moisture content. The prepared soap and plant extract exhibit good results against Baciluus cereus at a concentration of 150µg/mL (30.97 ± 0.2 and 25.7 ± 0.7). At the maximum concentration of 150µg/mL, the plant extract and herbal soap showed growth inhibition of 34.95 ± 0.72mm and 28.6 ± 0.68mm against A. niger, respectively, and 36.9 ± 0.44mm and 23.65 ± 0.15mm against A. flavus. Soap shows good result against A. flavus while plant extract shows good result against A. niger at the concentration of 150µg/ml. As a negative control, DMSO was used. In test tubes used as positive controls (terbinafine), no fungal growth was seen. Plant extract and specially manufactured soap maximum scavenging capacities of 41% and 61% at 150 g/ml concentration. These results showed that the formulated herbal soap is suitable for skin and can be a therapeutic alternative to skin problems.